SECLUSION AND WORK: RELATIONSHIP, LOGIC AND ARTICULATION IN THE DEVELOPMENT OF CHILEAN PRISON - Romero Miranda, Alejandro (2023)
This documentary research of a qualitative nature, aims to establish the legal and criminal discourses that give meaning to the work of prisoners in the five main forms of imprisonment evidenced in Chile between 1830 and 2000 - the confinement on Juan Fernández Island, the penal colony of Magallanes, the rural prisons, the mobile prison and the Penitentiary of Santiago-, for which, we proceeded to review of laws, regulations, writings and research related to each form of imprisonment. The analysis task was carried out through a thematic mesh and the hermeneutical tradition to order the information (triangulation). The results show that the work is conceived as an additional or complementary punishment to the sanction, a discourse that only changes after the installation of the penitentiary in 1843, where the inmate’s labor activity ceases to benefit others, focusing on the inmate himself. This change, however, does not encourage inmates to work due to the image of abuse and submission that they assign to their execution, and the birth of a prison subculture that will structure a masculinity and a reckless and stubborn criminal duty-being (conclusion).